The Solution to Enhance Quantitative Effect for Graders to Enter the Technical - Vocational Education and Training in Ho Chi Minh City - Nguyễn Trần Nghĩa, (Journal of Technical Education Science, 2007)
Nowadays, the grader’s awareness of occupation is not clear, especially about the characteristic of every profession comparing with the physical and psychological features of oneself. Besides, the psychological pressure from the residents of Ho Chi Minh city is that one must enter university. Therefore, in order to surmont the unbalance in training structure, we must organize vocational guidance, test and consult profession for graders, in order for them to have a clearer understanding about choosing a job appropriate with their abilities and the social needs. At the same time, we should create conditions for city youths to continue study at high levels by arccoding to consecutive programs among General education, Technical vocational education and training and University education. Carrying out the above-mentioned solutions will contribute effectively to enhancing quantiative effect for graders to enter the Technical vocational education and training.